Intermolecular Interaction of Hthyni Protein with Double Methylated DNA at 5m-Cytosine Nucleotide - Koirala, Rajendra Prasad; Khanal, Shyam Prakash; Shiwakoti, Sudip; Adhikari, Narayan Prasad (Journal of Institute of Science and Technology, 2020)
Human thymocyte nuclear protein 1 (hTHYN1) is one of the DNA binding proteins. It is essential for the regulation of Pax5 expression and the development of B cells in humans. Its thermodynamic and biological functions have been unclear yet. The study of the binding mechanism of hTHYN1 protein with DNA is essential to understand various biochemical functions in the human body. In this work, molecular dynamics (MD) simulations have been performed to understand the binding mechanisms of double methylated DNA (dmDNA) at cytosine nucleotide with hTHYN1 protein. Hydrogen bonding and other non-bonded (electrostatics and van der Waals) interactions among the residue-nucleotide pairs have been observed during the MD simulations and are also found responsible to form protein-DNA complex and to provide the stability of the structure. No salt bridges and hydrophobic interactions have been detected. Some of the protein residues in hTHYN1 have been found to strongly cooperate in the formation of the DNA-protein complex. Arginine residue of hTHYN1 has been observed as a major contributor in binding to the DNA. Many other residues also have significant roles in binding with DNA.